Multiplicative dependence of cubic algebraic numbers - Drungilas, Paulius; Klimavičius, Linas (Lietuvos matematikos rinkinys, 2017)
We provide an infinite family of cubic algebraic integers α such that the set α + x | x ∈ Z is multiplicatively dependent.